Prudential policy with distorted beliefs - Eduardo Dávila; Ansgar Walther (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper studies leverage regulation and monetary policy when equity investors and/or creditors have distorted beliefs relative to a planner. We characterize how the optimal leverage regulation responds to arbitrary changes in investors' and creditors' beliefs and relate our results to practical scenarios. We show that the optimal regulation depends on the type and magnitude of such changes. Optimism by investors calls for looser leverage regulation, while optimism by creditors, or jointly by both investors and creditors, calls for tighter leverage regulation. Monetary policy should be tightened (loosened) in response to either investors' or creditors' optimism (pessimism).
Keywords: G28; G21; E61; E52; 330; prudential policy; distorted beliefs; leverage regulation; bailouts; monetary policy